Developments in quality of stroke care in Estonia. (January 2023) - Kõrv, Janika; Antsov, Katrin; Gross-Paju, Katrin; Kalju, Inga; Kreis, Andrus; Liigant, Aive; Vibo, Riina
Background: Monitoring and measuring different aspects of stroke care pathway is the cornerstone for improvement of quality. We aim to analyze and give an overview of improvements of stroke care quality in Estonia. Patients and methods: National stroke care quality indicators are collected and reported using reimbursement data and include all adult stroke cases. In Estonia, five stroke-ready hospitals are participating in Registry of Stroke Care Quality (RES-Q), providing data on all stroke patients 1 month every year. Data from the national quality indicators and RES-Q from 2015 to 2021 are presented. Results: The proportion of intravenous thrombolysis for all Estonian hospitalized ischemic stroke cases increased from 16% (95% Confidence Interval, CI 15%–18%) in 2015 to 28% (95% CI 27%–30%) in 2021. Mechanical thrombectomy was provided to 9% (95% CI 8%–10%) in 2021. The 30-day mortality rate has decreased from 21% (95% CI 20%–23%) to 19% (95% CI 18%–20%). More than 90% of patients with cardioembolic stroke are prescribed anticoagulants at discharge, but only 50% are on anticoagulant treatment 1 year after stroke. Also, the availability of inpatient rehabilitation needs improvement, being 21% (95% CI 20%–23%) in 2021. A total of 848 patients are included in the RES-Q. The proportion of patients receiving recanalization therapies was comparable to the national stroke care quality indicators. All stroke-ready hospitals show good onset-to-door times. Conclusion: The overall stroke care quality in Estonia is good, especially the availability of recanalization treatments. However, secondary prevention and the availability of rehabilitation services need improvement in the future.